HAKIKAT DAN RUANG LINGKUP KAJIAN MULTIDISIPLIONER MATERI AQIDAH AKHLAK - Suhiroh, Iroh; Kurniawan, Ade Fakih (Public Sphere: Jurnal Sosial Politik, Pemerintahan dan Hukum, 2022)
The purpose of this study is to find out more about the Nature and Scope of Multidisciplinary Studies on Aqidah, Morals, Normative and Sociological Religious Perspectives. This research is library research. The data sources are taken from various literatures, both books, articles, magazines and so on. The data that has been collected was analyzed using descriptive analysis. The results of this study reveal that a multidisciplinary approach which is intended as a study or study using various scientific approaches that are placed in parallel, but has not been integrated in an integrative way. The scope of the Aqidah Study is; Divineyat, Nubuwat, Ruhaniyat, Sam'iyyat. While the scope of morality includes morals to God, to oneself, to society and morals to the environment. The moral improvement of the normative religious perspective is through perspective, dialogue, relations, interaction, interconnection, comparison, and collaboration. While the sociological approach is building morals that emphasizes the approach of social conditions and conditions by understanding the reciprocal relationship between individuals so as to create a peaceful life